Statistical test for interaction of G x E on QPM grain yellow for hybrid candidate under lowland in Indonesia. Issue 1 (April 2020) - Jamaluddin,; Isnaini, Muzdalifah; Faesal,; Yasin HG, M
Abstract: The use of the statistical test has been demonstrated to assess the interaction of single crosses QPM maize genotypes (G) under five different environments (E). The statistical pooled model used in this study i.e. yi= μ+τ+α+ε and (2) yij=μ+τ/Λ+α+(αxΛ)+ε, (effect of mean, replication within the location, entry, interaction gxe, error). The parental material was introduced from CIMMYT Maize Lines (CML) and the yellow grain tester was modified by MR14x CML164 backcrosses programs until BC3F3. The testing environment (ei, i=1, 2, 3, 4, 5) were lowland zone in (e1) Maros experimental Farm, (e2) Bajeng, (e3) Bontobili, (e4) Sidondo and (e5) Polman farmers field. Experiments were conducted by a randomized complete block design with three replications. The first variables were analyzed separately in each ei (i:1, 2, 3, 4, 5) and followed by pooled analysis by gj (j:1, 2, 3, . . ., 10). There were ten variables observed, the grain yield was observed in water content (wc) of 15%. The spacing used was 75x20cm one plant per space, the fertilizer applied were urea-ponska (200-150 kg/ha), weeding and irrigated was regularly conducted for maximum plant growth. The experiments were conducted on the rainy season in 2018. The statistical test showed that there is a significant difference of genotypes under five environments, interaction gxe, and cv: 10.69%, test by LSD (least significant difference) found that two candidates single cross (1)CML161-2-1-4-2xMR14Q and (2)CML165-3-1-2-4xMR14Q were high yielded and significantly different with two check variety MSQ.C0xMR14Q and Bima 13Q. These two single crosses could be promising as new QPM hybrids with yield potential 9.0-10.0 t/ha. The ear position is on the middle of the plant, shelling 75.2-77.8%, flowering 55 days and plant aspect scored one. QPM (Quality Protein Maize/Maize) is defined as speciality maize which has a high content of lysine and tryptophan. These are two essential amino acids that have important nutritional values for the human body to anticipate the disease among children and could be supplemented for human diets.